Solving the Equation (x-8)(x+3) = 0
This equation represents a quadratic equation in factored form. To find the solutions for x, we can use the Zero Product Property.
Zero Product Property
The Zero Product Property states that if the product of two or more factors is equal to zero, then at least one of the factors must be equal to zero.
Applying the Property
In our equation, we have two factors: (x-8) and (x+3). To make the product equal to zero, at least one of these factors must be zero.
Therefore, we have two possible scenarios:
-
(x-8) = 0 Solving for x, we get: x = 8
-
(x+3) = 0 Solving for x, we get: x = -3
Solutions
Therefore, the solutions to the equation (x-8)(x+3) = 0 are x = 8 and x = -3.
Verification
We can verify our solutions by plugging them back into the original equation:
- For x = 8: (8-8)(8+3) = 0 * 11 = 0. This is true.
- For x = -3: (-3-8)(-3+3) = -11 * 0 = 0. This is also true.
Therefore, our solutions are correct.